Democratizing money - Jan A. Kregel (Levy Economics Institute of Bard College, 2019)
In the Western interpretation of democracy, governments exist in order to manage relations of property, with absence of property ownership leading to exclusion from participation in governance and, in many cases, absence of equal treatment before the law. Democratizing money will therefore ensure equal opportunity to the ownership of property, and thus full participation in the democratic governance of society, as well as equal access to the banking system, which finances the creation of capital via the creation of money. If the divergence between capital and labor-between rich and poor-is explained by the monopoly access of capitalists to finance, then reducing this divergence is crucially dependent on the democratization of money. Though the role of money and finance in determining inequality between capital and labor transcends any particular understanding of the process by which the creation of money leads to inequity, specific proposals for the democratization of money will depend on the explanation of how money comes into existence and how it supports capital accumulation.
Keywords: E42; E51; E52; 330; Money; Finance; Financial History; Clearing Systems; Unit of Account